PENGEMBANGAN OBYEK WISATA AIR TERJUN ELONG TUNE YANG BERKELANJUTAN DI DESA LANTAN: TANTANGAN DAN STRATEGI - Hakim, Lukman; Nanda, Siluh; Fitriyani, Lyan; Alawwiyah, Waringin Febriana (Universitas Mataram, 2023)
This study discusses the challenges and strategies in the Development of a Sustainable Elong Tune Waterfall Tourism Object in Lantan Village. Tourism development is a series of actions that are planned and carried out to increase the potential attractiveness of a particular location or area so that it becomes an attractive tourist destination for visitors. Elong Tune Waterfall is managed by a group of residents who were previously managed voluntarily. The aim of the research is to explore various obstacles and challenges, as well as to formulate strategies for developing these tourism objects. The development of these tourism objects is faced with various obstacles that can hinder the development process. This constraint factor is a challenge that must be overcome through careful planning, collaboration between various stakeholders, and flexibility in adapting development strategies according to changing conditions and needs. The results of the analysis identified 11 factors that became obstacles, then the derivation became 9 internal factors that became challenges. The strategies that can be taken to overcome these challenges are the strategies that need to be taken as many as 11 strategies in developing village tourism objects.